Design and simulation of DC distributed power supply with power balance control technique - Uthen Kamnarn; Jedsada Yodwong; Pratch Piyawongwisal; Pakawadee Wutthiwai; Anon Namin; Phatiphat Thounthong; Noureddine Takorabet (Institute of Advanced Engineering and Science, 2022)
This paper presents the analysis, design and simulation of DC distributed power supply controlled with power and energy balance control technique. The proposed system consists of 5 connection structures of DC to DC converters which are parallel, cascade, source splitting, load splitting, and stack. The system mathematical model is analyzed by the average small-signal method. The proposed power balance control technique is used in the instance where the main sources supply the load of the system. The energy balance control technique is used in the case that the load at the 24 V and 12 V bus is backed up with a battery. The DC Distributed system is simulated by MATLAB/Simulink. The system has 1 kW power rating and contains 6 voltage bus with voltage ratings of 380, 100, 60, 48, 24, and 12 V. The simulation results show that, with the proposed power balance design and control technique, the system provides good dynamic responses and stability. In addition, the proposed technique simplifies the parameter design of the PI controller and solves the basic control limitations of the DC to DC converter.